A Wavelength Tunable CW Orange-red Laser Source Based on Magnesium Oxide-doped Periodically-poled LiNbO3 in an Intracavity Sum-frequency Generation - Yang BAI (Medžiagotyra, 2020)
A watt-level continuous wave (CW) orange-red laser with wavelength tunable properties is experimentally implemented based on sum-frequency generation (SFG) in a composite cavity. The cavity is composed of an 880 nm laser diode (LD) side-pumped Nd: GdVO4 p-polarized 1062.9 nm cavity and a single-resonant optical parametric oscillator (SRO) of signal light using a magnesium oxide-doped periodically-poled LiNbO3 (MgO: PPLN) crystal with a poling period of 29.1 μm. In the overlap region of the two cavities, orange-red laser is generated by using a type-II critical phase-matched potassium titanyl phosphate crystal (KTP) crystal. In the temperature tuning range of the MgO: PPLN crystal (from 30 °C to 200 °C), the CW orange-red laser beams are generated in a tunable waveband from 612.24 nm to 620.72 nm (Δλ = 8.48 nm), corresponding to the mid-infrared idler light is also obtained with tunable wavelength from 4027.5 nm to 3708.2 nm (Δλ = 319.3 nm). At the lowest tuning temperature of 30 °C, the maximum CW output power of the orange-red laser at 612.24 nm and the idler light at 4027.5 nm are obtained, which are 1.145 W and 2.83 W, respectively.